Intradural extra-medullary spinal cord tumor after dorso-lumbar spine fixation following 12th dorsal vertebra burst fracture: A case report with literature review - Hussein Mohsin Hasan; Ali Tarik Abdul Wahid; Nabeel Al-Fatlawi; Arwa Jader; Sajjad ghanim Al-Badri; Danya Ali Tarik (Radiology Case Reports)
Intradural extramedullary spinal cord tumors are rare but can cause significant neurological symptoms. We present a case of a 23-year-old male who developed progressive bilateral leg pain and lower limb weakness 2 years after undergoing posterior spinal fixation for a T12 burst fracture. Magnetic resonance imaging (MRI) revealed an intradural extramedullary tumor at the site of the previous surgery. The patient underwent surgical excision of the tumor, which was confirmed to be a Schwannoma. Postoperatively, the patient experienced significant improvement in both motor function and pain. This case underscores the importance of thorough follow-up care in patients with spinal trauma and fixation, as delayed secondary pathologies, such as spinal tumors, can occur.